Design and experimental study on a novel sealing structure of rotary control head for coalbed methane underbalanced drilling. (September 2022) - Liu, Yang; Qian, Liqin; Xia, Chengyu; Yi, Xianzhong
Highlights: The experimental study of new sealing rubber was carried out. The calculation of reliability of the new rubber core was carried out. The experimental research of combined seal are carried out. The reliability and superiority of the new sealing structure are verified on site. Abstract: In order to reduce the failure accidents of dynamic seal ring and rubber core of conventional rotary control head, a novel rotary control head for coalbed methane underbalanced drilling is developed in this paper. According to the material selection requirements of the rubber core and dynamic seal assembly, the mechanical properties experiments of hydrogenated nitrile rubber materials with three different formulations were carried out. According to the design scheme of the rotary control head, the toothed slip ring combined seal is selected, and the finite element analysis and experimental research are carried out on the seal. Finally, through the field test, the working performance of the novel special rotary control head for coalbed methane is tested. The experimental results show that there is no leakage in the static and dynamic sealing system during the application period. It shows that the designed sealing system is reliable.